EFFICACY AND SAFETY OF SOME ETIOTROPIC THERAPEUTIC SCHEMES FOR TREATING PATIENTS WITH NOVEL CORONAVIRUS INFECTION (COVID-19) - L. A. Balykova; V. F. Pavelkina; N. V. Shmyreva; N. A. Pyataev; N. M. Selezneva; O. I. Shepeleva; R. Z. Almyasheva (Фармация и фармакология (Пятигорск))
The aim of the study is to assess the efficacy and safety of the Favipiravir (Areplivir) drug, compared to the standard etiotropic therapy in the patients hospitalized with COVID-19.Material and methods. The research was conducted as a part of an open, randomized, multicenter comparative study of the efficacy and safety of Areplivir, 200 mg film-coated tablets (“PROMOMED RUS” LLC, Russia), in the patients hospitalized with COVID-19. The dosing regimen of Favipiravir was 1600 mg twice a day on the 1st day and 600 mg twice a day on days 2–14. Thirty nine patients were enrolled into the study with a laboratory-established diagnosis of a new type of Coronavirus infection caused by SARS-CoV-2 (confirmed) of moderate severity, with pneumonia. The group of comparison (22 patients) received standard etiotropic therapy, prescribed in accordance with the current version of the temporary guidelines for the diagnosis and treatment of COVID-19, represented mainly by Hydroxychloroquine with the dosage regimen of 800 mg on the 1st day, then 400 mg on days 2–7, and Azithromycin 500 mg once a day for 5 days. The main group (17 patients) received Favipiravir (Areplivir) as etiotropiс therapy.Results. In the main group, the time period until fever disappeared was found to be 1.36 days shorter than in the group of comparison (p<0.05); there was a higher rate of the reduction of inflammatory changes in the lungs according to the computer tomography data (38.4% vs 14.9%, p<0.05). By the end of the treatment, there was also a lower lactate level in the blood (27.1%, p<0.05) than in the patients of the group of comparison. The evaluation of the drug efficacy ассording to the Categorical Ordinal Scale of Clinical Improvement and measurements of oxygen saturation in the blood, manifested similar positive dynamics in the patients treated ассording to various etiotropic therapy regimens. By the end of the treatment, the RNA SARS-CoV-2 tests were also negative in all the patients. As for the overall frequency of adverse events (AEs), no relevant distinctions were found between the groups. A greater part of AEs was related to hepatotoxicity, with a predominantly clinically relevant increase in alanine aminotransferase (ALT). A clinically relevant prolongation of the corrected QT interval on the standard ECG was found to occur in the standard-therapy group on day 5, while no serious AEs were registered in the main group. No serious adverse reactions were registered in patients of the main group.Conclusion. The efficacy of the Favipiravir (Areplivir) therapy for the novel coronavirus infection has proved to be superior to the efficacy of the standard etiotropic therapy in a number of aspects. Basing on the obtained findings, Favipiravir (Areplivir) drug can be recommended for treating patients with the novel coronavirus infection of moderate severity.